Intrinsic responses to Borna disease virus infection of the central nervous system - Morimoto, Kinjiro (The National Academy of Sciences of the USA, 1996)
Immune cells invading the central nervous system (CNS) in response to Borna disease virus (BDV) antigens are central to the pathogenesis of Borna disease (BD). We speculate that the response of the resident cells of the brain to infection may be involved in the sensitization and recruitment of these inflammatory cells. To separate the responses of resident cells from those of cells infiltrating from the periphery, we used dexamethasone to inhibit inflammatory reactions in BD. Treatment with dexamethasone prevented the development of clinical signs of BD, and the brains of treated animals showed no neuropathological lesions and a virtual absence of markers of inflammation, cell infiltration, or activation normally seen in the CNS of BDV-infected rats. In contrast, treatment with dexamethasone exacerbated the expression of BDV RNA, which was paralleled by a similarly elevated expression of mRNAs for egr-1, c-fos, and c-jun. Furthermore, dexamethasone failed to inhibit the increase in expression of mRNAs for tumor necrosis factor α, macrophage inflammatory protein 1β, interleukin 6, and mob-1, which occurs in the CNS of animals infected with BDV. Our findings suggest that these genes, encoding transcription factors, chemokines, and proinflammatory cytokines, might be directly activated in CNS resident cells by BDV. This result supports the hypothesis that the initial phase of the inflammatory response to BDV infection in the brain may be dependent upon virus-induced activation of CNS resident cells.